STRUCTURAL RISK-BASED UNDERWATER INSPECTION (RBUI) AS A COST REDUCTION OF FIELD’s END OF PRODUCTION LIFE - Putra, Ivan Fitrian; Soedarsono, Johny Wahyuadi; Mahendra, Mirza; Haidir, Yuki; Purnawarman, Faisal Dwiyana; Sukirna, Iwan; Hernowo, Widi (Journal of Materials Exploration and Findings, 2022)
Mubadala Petroleum operates offshore platforms in a southern Makassar Straits that needs to be periodically inspected. The cost for the inspection is massive due to the high cost of mobilization and demobilization of vessels including crew and equipment. In response of a new approach to reduce cost, a Risk-Based Underwater Inspection (RBUI) methodology is developed. This RBUI purpose is to reduce the inspection interval of the offshore platform, from every 2 years to a longer period[1]. There are existing RBUI methodologies, which are already developed and implemented in other companies[5]. Purpose of this paper is to develop further detailed and more accurate RBUI methodology based on data analysis and the agile development method. Offshore platforms condition is dynamic and always changing from time to time. This methodology uses offshore platform design and condition data, including inspection data. All collected inspection data of offshore platform conditions will produce an accurate risk register of the platform. Thus, accurate risk register will give the best inspection interval time, considering its safety and economical benefit. From the RBUI analysis using this method, inspection interval can be deferred from 2 (two) years to range of 4-9 years, depending on the condition and risk of the platform. The operating cost of each platform also reduced up to US$ 670,737 per year.